1995
DOI: 10.1074/jbc.270.15.8466
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phospholipase D in HL60 Cells

Abstract: Phospholipase D (PLD) activity that was stimulated by guanosine 5'-O-(3-thiotriphosphate) (GTP gamma S) was detected in cytosol and membranes of HL60 cells. GTP gamma S-stimulated PLD activity was detected in the membranes when exogenous labeled phosphatidylcholine was used in the presence of phosphatidylethanolamine and phosphatidylinositol 4,5-bisphosphate, but not when [3H]myristic acid-labeled endogenous substrate was used. Cytosolic PLD co-chromatographed with small GTP-binding proteins on anion-exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 37 publications
5
88
1
Order By: Relevance
“…Stabilization of this interaction would yield increased activity of the enzyme, whereas disruption would inhibit activity. Enhancement of interaction of the C terminus with the active site would be a means for one or more activators of PLD1 to exert their stimulatory effects, especially synergism observed by combinations of activators (16,19,20,22,43,44). The apparent deficient recovery of stimulation with Rho, which is thought to interact with C-terminal regions of PLD (31,32), is consistent with such a mechanism.…”
Section: Discussionmentioning
confidence: 54%
“…Stabilization of this interaction would yield increased activity of the enzyme, whereas disruption would inhibit activity. Enhancement of interaction of the C terminus with the active site would be a means for one or more activators of PLD1 to exert their stimulatory effects, especially synergism observed by combinations of activators (16,19,20,22,43,44). The apparent deficient recovery of stimulation with Rho, which is thought to interact with C-terminal regions of PLD (31,32), is consistent with such a mechanism.…”
Section: Discussionmentioning
confidence: 54%
“…HL60 cells were purchased from ATCC and maintained as described (17). COS7 cells were purchased from ATCC and grown in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum, 50 units/ml penicillin, and 50 g/ml streptomycin at 37°C in a humidified atmosphere of 10% CO 2 and 90% air.…”
Section: Yeast Strain and Cell Lines-mentioning
confidence: 99%
“…Miscellaneous Procedures-SDS-PAGE and Western blotting were performed as described (17) except that an ECL kit (Amersham Corp.) was used for detection. Protein concentrations were determined using the Coomassie Plus protein assay reagent (Pierce) with bovine serum albumin as a standard.…”
Section: The Nucleotide Sequence(s) Reported In This Paper Has Been Smentioning
confidence: 99%
“…In addition, there may be multiple forms of small G protein-dependent PLD including ARF-sensitive, RhoA-sensitive, and ARF-, RhoA-sensitive PLDs. Siddiqi et al (14) reported that the cytosolic fraction of HL-60 cells contained a soluble PLD activated by ARF, but not RhoA. Malcolm et al (8) showed rat liver plasma membrane PLD to be sensitive to RhoA, but not to ARF.…”
mentioning
confidence: 99%